Postpartum sexually transmitted disease: refining our understanding of the population at risk. - Wheeler, Rebekah; Earnshaw, Valerie A; Kershaw, Trace; Ickovics, Jeannette R (Sexually transmitted diseases, 2012)
Scant literature exists on sexually transmitted disease (STD) risk specific to pregnancy and postpartum. The objective of this prospective study is to examine risk factors for incident postpartum STDs among young mothers (ages, 14-25).
Keywords: Adolescent; Adult; Educational Status; Female; Health Knowledge, Attitudes, Practice; Humans; Infant, Newborn; Postpartum Period; Pregnancy; Pregnancy Complications, Infectious; Pregnancy in Adolescence; Prenatal Care; Prevalence; Prospective Studies; Risk Factors; Sexual Behavior; Sexual Partners; Sexually Transmitted Diseases; Socioeconomic Factors; Substance-Related Disorders; United States; Young Adult